Studies about rearing six species of butterflies from the lower Anchicayá (Valle) and knowledge contributions of their natural history - PRIETO, AÍDA VIVIANA; CONSTANTINO, LUIS MIGUEL; CHACÓN DE ULLOA, PATRICIA (Revista Colombiana de Entomología, 1999)
information about the life cycle for six species of butterflies from the lower Anchicaya river is presented: Banus chalceus ingenuus(Dyar, 1907). Heliconious cydnoalinde (Butler, 1869), Erachlides anchiciades(Esper. 1788), Parides childrenae latifasciata(Krugcr, 1925), Parides eurimedes emilins (Constantino. 1998) y Paride.s. pallares eruthrus ( Rothschi Id y Jordan, 19061. belonging to Fiel Heliconidae and Papilionidae. The herbivory indexes are presented for Paride euriwedess and Heliconious edno. Information about the monitoring of a population of butterflies as an indicator group is given, as a strategy for conserving and managing wild populations integrated within a rearing program with rural communities.